DETERMINASI KOMPENSASI KERUGIAN FISKAL DAN PERTUMBUHAN PENJUALAN TERHADAP TAX AVOIDANCE - Widilestariningtyas, Ony; Kristina, Entin (Jurnal Riset Akuntansi, 2023)
Tax is a burden that will reduce net profit so companies will look for ways to minimize the tax burden and one of the actions is through Tax Avoidance. Companies that experience losses can encourage Tax Avoidance, especially in mining companies. This study aims to determine compensation for fiscal losses and sales growth for Tax Avoidance in four (4) mining companies listed on the Indonesia Stock Exchange in 2015-2022. The data analysis method used is multiple linear regression analysis with SPSS version 23. The results of this study indicate that partially the variable compensation for fiscal losses and sales growth has a significant positive effect on Tax Avoidance.